ANALISIS KONTRIBUSI PRODUKSI BUAH LOKAL MALUKU UTARA SEBAGAI INANG ALTERNATIF CHRYSOMPHALUS AONIDUM - Arief Widyantoro; Supriyono Supriyono (LPPM Universitas Negeri Jakarta, 2019)
ABSTRACT Chrysomphalus aonidum is an important pest in fruits. Maluku Utara is a free area of ​​C. aonidum so that any entry of fruit from outside the area must be accompanied by a phytosanitary certificate from the area of ​​origin. Local fruit products have a potential to develop as export commodities, given their large numbers and variety. Problems arised when the larger volumes of fruits imports without going through quarantine measured on fruit products contaminated with pests and diseases can attack Indonesian local fruit commodities. The research was aimed to study the contribution of local fruit production to national production and its potential as an alternative host of C. aonidum. The study was used Trend Model Time Series and Location Quotient (LQ) analysis to discuss the changes of agricultural commodity. The results showed that bananas, melons and oranges have the potential to be the main hosts of C. aonidum while the nutmeg and cacao commodities are alternative hosts. Concentrated local fruit cultivation in a particular area has a greater impact on handling if attacked by C.aonidum than scattered cultivation.